The Third Man: comparative analysis of a science autobiography and a cinema classic as windows into post-war life sciences research - Zwart, Hub (Hist Philos Life Sci, 2015)
In 2003, biophysicist and Nobel Laureate Maurice Wilkins published his autobiography entitled The Third Man. In the preface, he diffidently points out that the title (which presents him as the ‘third’ man credited with the co-discovery of the structure of DNA, besides Watson and Crick) was chosen by his publisher, as a reference to the famous 1949 movie no doubt, featuring Orson Welles in his classical role as penicillin racketeer Harry Lime. In this paper I intend to show that there is much more to this title than merely its familiar ring. If subjected to a (psychoanalytically inspired) comparative analysis, multiple correspondences between movie and memoirs can be brought to the fore. Taken together, these documents shed an intriguing light on the vicissitudes of budding life sciences research during the post-war era. I will focus my comparative analysis on issues still relevant today, such as dual use, the handling of sensitive scientific information (in a moral setting defined by the tension between collaboration and competition) and, finally, on the interwovenness of science and warfare (i.e. the ‘militarisation’ of research and the relationship between beauty and destruction). Thus, I will explain how science autobiographies on the one hand and genres of the imagination (such as novels and movies) on the other may deepen our comprehension of tensions and dilemmas of life sciences research then and now. For that reason, science autobiographies can provide valuable input (case material) for teaching philosophy and history of science to science students.